2010
DOI: 10.1038/emboj.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of Rad17 by Cdh1/APC regulates checkpoint termination and recovery from genotoxic stress

Abstract: Recent studies have shown a critical function for the ubiquitin-proteasome system (UPS) in regulating the signalling network for DNA damage responses and DNA repair. To search for new UPS targets in the DNA damage signalling pathway, we have carried out a non-biased assay to identify fast-turnover proteins induced by various types of genotoxic stress. This endeavour led to the identification of Rad17 as a protein exhibiting a distinctive pattern of upregulation followed by subsequent degradation after exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 49 publications
2
65
1
Order By: Relevance
“…We confirmed that MG132 inhibits UV irradiation-induced Rad17 degradation as reported previously (Fig. 5E) (21). The amount of Rad17 was increased by SFK inhibition in Fig.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointsupporting
confidence: 79%
See 1 more Smart Citation
“…We confirmed that MG132 inhibits UV irradiation-induced Rad17 degradation as reported previously (Fig. 5E) (21). The amount of Rad17 was increased by SFK inhibition in Fig.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointsupporting
confidence: 79%
“…Because the stability of Rad17 is regulated by proteasome-dependent protein degradation during checkpoint recovery (1)(2)(3)21), the involvement of proteasomal protein degradation was examined. Exposure to the proteasome inhibitor MG132 did not affect the increase in Rad17 phosphorylation induced by SU6656 (Fig.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointmentioning
confidence: 99%
“…We have identified USP20 as a new player in the DDR by stabilizing Rad17. The enhanced interaction between USP20 and Rad17 after DNA damage is probably required to protect RAD17 from the excessive ubiquitylation that occurs in this situation (9). The increased in vivo Rad17 ubiquitylation when USP20 is depleted, the in vitro activity of USP20 on UbRad17, the reversal of Rad17 instability in the presence of a proteasome inhibitor, and the requirement of USP20 catalytic domain for Rad17 stability; all point to a direct enzymatic effect of USP20 on Rad17 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Rad17 protein was reported to be regulated by the ubiquitin-proteasome system (UPS) (9). The anaphase-promoting complex (APC) was identified as the ubiquitin E3 ligase that mediates Rad17 degradation (9). In this report we implicate a novel Dub, ubiquitin-specific peptidase 20 (USP20), in the DDR by interacting with and regulating the protein level and function of Rad17.…”
mentioning
confidence: 89%
See 1 more Smart Citation